Analisis Tindak Tutur pada Pengemudi Ojek Online (OJOL) - Diana; Juli Arihta; Nila Angita; Nailah; Rowimatul; Sarah Br Ginting; Sry Eninta; Welia Sigalingging; Oky Fardian (Universitas Serambi Mekkah, 2025)
Speech acts are the main unit of analysis in pragmatics that highlights how hidden meanings and intentions are constructed in real communication. This study aims to analyze the forms of locutionary, illocutionary, and perlocutionary speech acts used by online motorcycle taxi (ojol) drivers in daily interactions with passengers. The research method used is qualitative method with data collection techniques through direct observation and semi-structured interviews with ojol drivers in Medan city. The interview was conducted on the way from Medan State University to Podomoro City Mall, then the data obtained were recorded and analyzed. The results show that locutionary acts function to convey information literally, illocutionary acts contain certain intentions or goals that speakers want to achieve, and perlocutionary acts cause effects or influences on interlocutors. Conversational analysis shows that simple interactions between students and ojol drivers contain complex communication dynamics, not only exchanging information but also building understanding and influencing attitudes. In conclusion, speech acts in ojol drivers' conversations reflect that verbal communication involves deep cognitive, social, and pragmatic processes, while reinforcing the role of language in building social relationships in a professional context.